Comparison of ophthalmic artery Doppler indices among hypertensive and normotensive pregnant women in third trimester: association with perinatal outcomes - Manchu, Madhuri; Reddi, Geeta Vandana; M., Ravali Ranjith (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: In this study, we compared ophthalmic artery Doppler indices between normotensive and hypertensive pregnant women in third trimester and then evaluated if the alterations in ophthalmic artery doppler indices were seen in all the types of hypertensions in pregnancy or confined to preclaampsia. Further we tried to see correlation of ophthalmic artery Doppler indices with perinatal outcomes in terms of fetal growth restriction (FGR), prematurity, neonatal intensive care unit admission (NICU) and maternal outcomes and tried to arrive at mean values of ophthalmic artery Doppler indices to predict adverse outcomes. Methods: 50 hypertensive and 50 normotensive pregnant women were recruited in third trimester. A thorough history about hypertension was taken, obstetric scan was done to know estimated fetal weight, and doppler of umbilical, middle cerebral artery, uterine arteries was done. Simultaneously maternal ophthalmic artery Doppler readings were taken, women were followed up after delivery and perinatal outcomes were recorded. Results: Comparison of mean values of ophthalmic artery doppler parameters in women with and without hypertension showed statistically significant differences with respect to the peak systolic velocity 2 (PSV2), PI (pulsatility index), RI (resistivity index) and peak ratio (PR) (PR=PSV2/PSV1). Significant difference was found only in PR value in preeclampsia group compared to other subgroups of hypertension. In the hypertension group complicated with FGR the mean peak ratio=0.8 whereas in the hypertension group requiring preterm delivery the mean peak ratio=0.78, and in the hypertension group requiring NICU admission the mean peak ratio=0.81. At ophthalmic artery PR cut off ≤0.725, the sensitivity and specificity were 76% and 65% respectively to predict FGR. Conclusions: Pregnancy complicated by hypertension showed alterations in ophthalmic artery Doppler indices. Among the subgroups of hypertension, ophthalmic artery PR was the best index for discriminating preclampsia from other types and it was significantly higher in hypertensive pregnant women who had adverse perinatal outcomes. Ophthalmic artery PR has almost similar performance as uterine artery PI in indicating FGR in our study. It could also indicate maternal disease severity such as hypertensive crisis requiring ICU admission, the study number was small.